PUBLICATIONS AND TRENDS OF RESEARCH IN FOREIGN LANGUAGE MAJORS AT VNU UNIVERSITY OF LANGUAGES AND INTERNATIONAL STUDIES: A PRELIMINARY SURVEY - Van, Hoang Van (VNU Journal of Foreign Studies; Vol 33 No 6, 2017)
In this paper, an attempt is made to conduct a survey on the publications and research trends in foreign language majors at University of Languages and International Studies – Vietnam National University, Hanoi (VNU ULIS). The survey data includes articles by VNU ULIS academics published in Vietnamese prestigious specialized journals, theses and dissertations by master and doctoral students. The survey reveals some noticeable fndings: (1) there are very few articles by VNU ULIS academics published in prestigious Vietnamese journals; (2) of the two felds of study recognised as the mandate of VNU ULIS as represented in its English name: foreign language studies and international studies, the latter has not yet gained its status on the same par as the former; and (3) between the two subfelds of foreign language studies: foreign language education and foreign language linguistics, the former dominates the research scene at master level, but at doctoral level the two felds of research seem to be equally attended to. The fndings of the survey also show that different foreign language majors seem to focus on different felds of research, making it diffcult to state which feld is the main trend of research at present and which one will be the main trend of research in the years to come.